FLEXIBILIDADE NA ARQUITETURA: MAPEAMENTO SISTEMÁTICO DE LITERATURA EM BASES BRASILEIRAS - Logsdon, Louise; Costa, Heliara; Fabricio, Márcio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research aims to perform a Systematic Mapping of Literature on Flexibility, in order to classify articles published in national scientific journals and proceedings. The methods of conduction followed four steps: (1) definition of the research protocol; (2) identification of articles; (3) selection of articles and (4) extraction of information. In addition to listing the number of articles according to event/journal, year, authors and institutions, the results bring the classification of articles into five pre-established criteria: focus, typology, objectives, methods and contributions.